Governance and business models for sustainable capitalism - Midttun, Atle, 1952- (Routledge studies in management, organizations and society, 2022)
"Governance and Business Models for Sustainable Capitalism touches upon many of the central themes of today's debate on business and society. In particular, it brings attention to a recurrent tension between efficiency, innovation and productivity on the one hand, and fairness, equity and sustainability on the other. The book argues that we need radical rethinking of business models and economic governance, beyond the classical doctrine which sees social and ecological responsibility as lying with public policy regulation of purely profit-seeking firms. In spite of the popular CSR agenda, business - as we know it today - is both too transient and too limited in its motivation to carry the regulatory burden. We need to adopt a much wider concept of "partnered governance", where advanced states and pioneering companies work together to raise the social and environmental bar. The book suggests that civil engagements based on moral rather than formal rights, and amplified through the media, may provide a healthy challenge both to autocratic planning and to solely profit-centered commercialization. The book also proposes a triple cycle theory of innovation for sustainability: a novel framing of the efficacy of green and prosocial entrepreneurship as intertwined with political visions and supportive institutions. In addition, the book offers reflections on the ways in which further digital robotizaton may enable transition to an 'Agora Economy' where productive efficiency is combined with expanded civic freedoms. Aimed primarily at researchers, academics and students in the fields of political economy, business and society, corporate governance, business ethics, corporate social responsibility and sustainability, the book will additionally be of value to practitioners, supplying them with information regarding the challenges associated with the shaping of sustainable or 'civilised' market capitalism for a better world"--